A COMPREHENSIVE REVIEW ON IN SITU GELS - PADMASRI, BUDUMURU; NAGARAJU, RAVOURU; PRASANTH, DAMARASINGU (International Journal of Applied Pharmaceutics, 2020)
The current review on in situ gelling systems becomes one of the most popular and prominent. It had a tremendous potential advantage of delivery systems due to many benefits like easy to use simple manufacturing; improve both adherence and patient comfort by minimizing the frequency of drug administration by its unique characteristics feature of sol to gel transition. It also provides in situ gelling nanoemulsions, nanosphere, microspheres, and liposomes. The drawbacks associated with conventional systems of both solutions and gels, such as accurate dosing, ease of administration overcome by using in situ gelling systems. This review focused on definitions, types, advantages, disadvantages, polymers used, and suitable characteristics of polymers, including the preparation of in situ gels covered in the introduction. Approaches, applications, and evaluation of in situ gels were explained with examples.